ECOS DO MODERNISMO E DE MÁRIO DE SÁ-CARNEIRO NA REVISTA O OCIDENTE (1878-1914) - Müller, Fernanda Suely (Revista Desassossego, 2009)
Having as main theme the articles from/about the writer Mário de Sá-Carneiro that have been published at O Ocidente magazine (1878-1914), we want debate the Modernism’s divulgation realized by this review. We are looking for to delineate also what was the magazine’s interpretation about that new poetics aesthetics.